Pelaksanaan Pendidikan Karakter Religius Siswa di MAS Al-Madani Kecamatan Luhak Nan Duo Kabupaten Pasaman Barat - Rizky, Pricilia Eveline; Jasrial, Jasrial (Lembaga Yasin AlSys, 2023)
This research was motivated by problems found in the religious character education of students at MAS Al-Madani, Luhak Nan Duo District, West Pasaman Regency. This research aims to explore information about the Implementation of Student Religious Character Education at MAS Al-Madani, Luhak Nan Duo District, West Pasaman Regency in terms of Tolerance, Sincerity, Honesty, Responsibility and Cooperation. This type of research is quantitative descriptive. Total 66 students (population) and 66 people (sample). Sampling used a total sampling technique considering the number of samples was less than one hundred. The instrument used was a questionnaire with a Likert scale model with 48 items. The data collection instrument was carried out with five answer choices, namely Always (SL), Often (SR), Sometimes (KD), Rarely (JR), Never (TP). The implementation of students' religious character education seen from the Tolerance dimension obtained an average score of 4.05. The implementation of students' religious character education seen from the Honesty dimension obtained an average score of 3.86 in the good category. The implementation of students' religious character education seen from the Ikhlas dimension obtained an average score of 3.7 in the good category. Student services seen from the Collaborative Responsibility dimension obtained an average score of 3.78 in the good category. The implementation of students' religious character education seen from the Ikhlas dimension obtained an average score of 3.95 in the good category. Thus, it can be concluded that 5 indicators out of 11 sub-indicators achieved good criteria with an average score of 3.87.